Development of an electrochemical immunosensor using gold nanoparticles (AuNPs) for the detection of Apolipoprotein AI (ApoAI) in chicken blood plasma / Nurhazirah Azmi ... [et al.] - Azmi, Nurhazirah; Zainal Abidin, Siti Aimi Sarah; Low, Kim Fatt; Mahmud, Abdul Hadi; Gati, Nur Izzati; Karsani, Saiful Anuar (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
The research aims to develop an electrochemical immunosensing assay using gold nanoparticles (AuNPs) on screen printed carbon electrode (SPCE) for the specific detection of Apolipoprotein A1 (ApoA1) proteins in chicken blood plasma (CBP). The biotin anti-ApoAI antibody was first immobilized on magnetic beads (MBs), while antibody ApoA1 was then conjugated with AuNPs. After a series of sandwich-type immunoreaction complexes was performed on the screen-printed carbon electrode, AuNPs were quantified by subjecting the immunocomplex to a peroxidation process of high potential at 1.2 V for 330 s and immediately reduced and scanned by differential pulse voltammetry (DPASV). This study obtained a linear relationship between reduction peak current signals and ApoA1 concentration from 0 to 100% (correlation coefficient of 0.996 with a detection limit of 5% of chicken blood plasma (CBP). The efficacy of our immunosensor is predicated on the seamless integration of antibodies with MBs to the target analyte, which provide ample surface area, biocompatibility, and user-friendliness. This breakthrough improves preliminary food fraud detection's sensitivity, reliability, and usability. It could improve diagnostic food safety, leading to a worldwide health breakthrough.